Hypoxia‐induced secretion stimulates breast cancer stem cell regulatory signalling pathways. Issue 8 (26th June 2019) - Jacobsson, Hanna; Harrison, Hannah; Hughes, Éamon; Persson, Emma; Rhost, Sara; Fitzpatrick, Paul; Gustafsson, Anna; Andersson, Daniel; Gregersson, Pernilla; Magnusson, Ylva; Ståhlberg, Anders; Landberg, Göran
Abstract : It is well known that tumour cells are dependent on communication with the tumour microenvironment. Previously, it has been shown that hypoxia (HX) induces pronounced, diverse and direct effects on cancer stem cell (CSC) qualities in different breast cancer subtypes. Here, we describe the mechanism by which HX‐induced secretion influences the spreading of CSCs. Conditioned media (CM) from estrogen receptor (ER)‐α‐positive hypoxic breast cancer cell cultures increased the fraction of CSCs compared to normal growth conditions, as determined using sets of CSC assays and model systems. In contrast, media from ERα‐negative hypoxic cell cultures instead decreased this key subpopulation of cancer cells. Further, there was a striking overrepresentation of JAK‐STAT‐associated cytokines in both the ERα‐positive and ERα‐negative linked hypoxic responses as determined by a protein screen of the CM. JAK‐STAT inhibitors and knockdown experiments further supported the hypothesis that this pathway is critical for the CSC‐activating and CSC‐inactivating effects induced by hypoxic secretion. We also observed that the interleukin‐6‐JAK2‐STAT3 axis was specifically central for the ERα‐negative hypoxic behaviour. Our results underline the importance of considering breast cancer subtypes in treatments targeting JAK‐STAT or HX‐associated processes and indicate that HX is not only a confined tumour biological event, but also influences key tumour properties in widespread normoxic microenvironments. Abstract : Estrogen receptor‐alpha (ERα)–positive and ERα–negative breast cancer cells are exposed to hypoxia during tumorigenesis. Spreading of hypoxic signals takes place through secretion of crucial factors playing a pivotal role in the transformation into cancer stem cells (CSCs). The hypoxic ERα‐positive‐driven secretome contributes to expansion of CSCs, whereas the ERα–negative‐driven secretome have an inhibitory effect on cancer stemness.